2019
DOI: 10.1159/000500200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Heat Shock Factor 1 Enhances Repressive Molecular Mechanisms on the <b><i>POMC</i></b> Promoter

Abstract: Background: Cushing’s disease (CD) is caused by adrenocorticotropic hormone (ACTH)-secreting pituitary tumours. They express high levels of heat shock protein 90 and heat shock factor 1 (HSF1) in comparison to the normal tissue counterpart, indicating activated cellular stress. Aims: Our objectives were: (1) to correlate HSF1 expression with clinical features and hormonal/radiological findings of CD, and (2) to investigate the effects of HSF1 inhibition as a target for CD treatment. Patients/Methods: We examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…The HSF1 inhibitor KRIBB11 inhibited POMC transcription and ACTH synthesis in the AtT-20 cell line and in primary cultures from Cushing disease patients. As expected, this inhibitory action was mediated by increased GR and suppressed Nur77/ Nurr1 and AP-1 transcriptional activities (67). Therefore, HSF1 could be yet another potential drug target for the pharmacological treatment of Cushing's disease.…”
Section: Role Of Hsp90 In Cushing's Disease and Potential Treatment Wsupporting
confidence: 64%
See 1 more Smart Citation
“…The HSF1 inhibitor KRIBB11 inhibited POMC transcription and ACTH synthesis in the AtT-20 cell line and in primary cultures from Cushing disease patients. As expected, this inhibitory action was mediated by increased GR and suppressed Nur77/ Nurr1 and AP-1 transcriptional activities (67). Therefore, HSF1 could be yet another potential drug target for the pharmacological treatment of Cushing's disease.…”
Section: Role Of Hsp90 In Cushing's Disease and Potential Treatment Wsupporting
confidence: 64%
“…More recently, we showed that HSF1, the transcription factor that controls HSP90 transcription, is also highly expressed and active in Cushing tumours in comparison to the normal pituitary (67). The HSF1 inhibitor KRIBB11 inhibited POMC transcription and ACTH synthesis in the AtT-20 cell line and in primary cultures from Cushing disease patients.…”
Section: Role Of Hsp90 In Cushing's Disease and Potential Treatment Wmentioning
confidence: 97%